Exploring bacteria-induced growth and morphogenesis in the green macroalga order Ulvales (Chlorophyta) - Wichard, Thomas (Frontiers in Plant Science, 2015)
Green macroalgae, such as Ulvales, lose their typical morphology completely when grown under axenic conditions or in the absence of the appropriate microbiome. As a result, slow growing aberrant phenotypes or even callus-like morphotypes are observed in Ulvales. The cross-kingdom interactions between marine algae and microorganisms are hence not only restricted by the exchange of macronutrients, including vitamins and nutrients, but also by infochemicals such as bacterial morphogenetic compounds. The latter are a fundamental trait mediating the mutualism within the chemosphere where the organisms interact with each other via compounds in their surroundings. Approximately 60 years ago, pilot studies demonstrated that certain bacteria promote growth, whereas other bacteria induce morphogenesis; this is particularly true for the order of Ulvales. However, only slow progress was made towards the underlying mechanism due to the complexity of, for example, algal cultivation techniques, and the lack of standardized experiments in the laboratory. A breakthrough in this research was the discovery of the morphogenetic compound thallusin, which was isolated from an epiphytic bacterium and induces normal germination and restores the foliaceous morphotypes of Monostroma. Owing to the low concentration, the purification and structure elucidation of highly biologically active morphogenetic compounds is still challenging. Recently, it was found that only the combination of two specific bacteria from the Rhodobacteraceae and Flavobacteriaceae can completely recover the growth and morphogenesis of axenic Ulva mutabilis cultures forming a symbiotic tripartite community by chemical communication. This review combines literature detailing evidence of bacteria-induced morphogenesis in Ulvales. A set of standardized experimental approaches is further proposed for the preparation of axenic algal tissues, bacteria isolation, co-cultivation experiments, and the analysis of the chemosphere.